Revolutionizing Crystal Guava Production through Six Sigma and Kaizen Insights: Merevolusi Produksi Jambu Kristal melalui Wawasan Six Sigma dan Kaizen - Mauli, Fajar Dwi; Cahyana , Atikha Sidhi; Sukmono, Tedjo; Jakaria, Ribangun Bamban (Indonesian Journal of Innovation Studies, 2024)
This study addresses the quality issues in crystal guava production at UD Bumiaji Sejahtera using the Six Sigma and Kaizen methodologies. By analyzing factors like non-uniform maturity, black spots, fruit rot, shape defects, and seed defects, this research aims to identify key areas for improvement. Results indicate that non-uniform maturity contributes significantly to defects, highlighting the need for improved pest control, efficient application methods, regular maintenance, material inspection, and enhanced standards for farmers and agricultural workers. These findings offer practical insights for enhancing crystal guava production quality and reducing defects at UD Bumiaji Sejahtera. Highlight: Six Sigma and Kaizen for Crystal Guava Quality Enhancement. Non-uniform Maturity Identified as Key Defect Contributor. Recommendations: Improved Pest Control, Application Methods, and Standards for Farmers. Keyword: Crystal Guava Production, Six Sigma, Kaizen, Quality Improvement, Defect Reduction